Analysis and Classification Of Wireless LAN Network Service Quality Using The Naive Bayes Algorithm In The Department Of Informatics and Computer Engineering, Faculty Of Engineering, State University Of Makassar - Siti Justianti Muhajriyah; Ruslan; Firdaus (Penerbit Jurnal Indonesia, 2024)
This study aims to determine the Quality of Service outcomes and the classification results of the Naive Bayes Algorithm on the Wireless LAN network quality in the Department of Informatics Engineering and Computer Faculty of Engineering at Makassar State University. This study uses the Action Research method with a quantitative approach. It conducts 54 tests using Wireshark in two different sessions to be compared for each time conducted during the research. The results of the research indicate that the status of the Wireless LAN network in the Department of Informatics Engineering and Computer Faculty of Engineering at Makassar State University falls into the